Múltiplos olhares sobre a produção do conhecimento em educação especial - Maria Cristina Piumbato Innocentini Hayashi (Revista Diálogo Educacional, 2011)
The arti cle discusses the production of knowledge in special educati on focusing on approaches and epistemological aspects of the area, the att enti on to social demands in special educati on sponsored by the research, the theoreti cal construct, methodological procedures and the eff ecti veness of research results in this fi eld of knowledge. At the same ti me raises questi ons about how the knowledge produced in university may have an impact on the practi ce of inclusive educati on outside the walls of academia and how research can transform the reality of special educati on in Brazil today. Concludes with a discussion of the public or private incenti ves to encourage the producti on of knowledge in special educati on in Brazil.